Are root exudation or rainfall on treated plants likely causes of pasture damage after wiper application of herbicides? - Harrington, KC; Ghanizadeh, H; Moyo, C; Kemp, PD; Eerens, JPJ (Weeds Society of Western Australia)
Wiper application of herbicides to weeds sometimes causes damage to pasture plants, especially white clover, growing immediately under the wiped weeds. Two experiments were conducted to determine the potential for either exudation of herbicide from roots or rainfall washing herbicide off treated plants to cause damage to white clover after wiper application. In Experiment 1, Californian thistle and white clover were grown in the same pots within a glasshouse, then either metsulfuron or a triclopyr/picloram mixture were applied to the Californian thistle using a Rotowiper. White clover growing in pots below treated plants was significantly affected by the metsulfuron but not the triclopyr/picloram mixture, when compared with the untreated control plants. In Experiment 2, Californian thistle, white clover and perennial ryegrass were grown in separate pots within a glasshouse. Glyphosate, clopyralid, metsulfuron and a triclopyr/picloram mixture were applied to Californian thistle plants using a Rotowiper. The treated Californian thistle plants were then exposed to artificial rain from a rainfall simulator either 1 or 5 days after herbicide treatment, with pots of white clover and perennial ryegrass positioned under each Californian thistle plant during the rainfall event. All of the herbicides except glyphosate significantly affected white clover for both rainfall events, whereas only metsulfuron significantly affected perennial ryegrass for the Day 1 washing. Thus although damage from herbicide exudation does appear possible, rainfall following wiper applications is probably more likely to cause damage to clover growing under treated plants.